Rotavirus como agente causal de diarreas en niños/as menores de 5 años de Saraguro - Abad Ramírez, Carlos Alberto (2015)
International studies have demonstrated a high incidence of rotavirus etiologic in pediatric patients in developing countries, being a very common cause of hospitalization for acute diarrhea. The purpose of the following study was to determine the rotavirus as a causal agent of diarrhea in children under 5 years of Saraguro; analyze samples by Immunochromatographic methods that detects the presence of the rotavirus, being a modern method that has significantly increased its sensitivity and specificity for the confirmation of the etiological; determine the epidemiological factors that predispose to the contagion of the diarrheal syndrome; set the gender of children with acute diarrhea caused by rotavirus; to know the most frequent age in children with diarrhea caused by rotavirus; and, disseminate the results to the families of children with rotavirus diarrhea and to the general population, through the development of an informative brochure. This research is a descriptive and cross-sectional area was used as the research base hospital of Saraguro with a population of 60 children who participated under the consent of the parents, taking into account the inclusion and exclusion criteria, then carried out the study of the results obtained were 2 positive cases, a girl in an age of between 0 to 12 months and a child between 12 to 24 months for the 3.33 per cent and 58 were negative which corresponds to 96.67 %. We were able to determine that there is a moderate incidence of children infected with this disease and the main epidemiological factors that predispose to this type of infections established by the survey of parents of children under the age of 5 years are: in relation to the type of power is obtained that the 45% of the infants consume breast milk, 41, 67% normal food and infant formula, the 13.33 % breast milk and normal meal; in regard to the use of bottle stated that 30% of the children if you are using, while 70% do not make use of the same; so too the 16.67 % of those surveyed replied that washed the bottle 1 to 2 times, the 13.33 % From 3 to 4 times, and the 70% did not answer; 10% of the representatives replied that change the bottle of bottle every 2 months, the 6.67 % every 3 months, the 13.33 % every 4 months and 70% of the same preferred not to answer; the 23.33 per cent mentioned that the bottle remains capped after its use, the 6.67 % does not remain capped and 70% did not answer. It was able to observe the presence of the etiological Rotavirus in children under the age of 5 years, that is why it is important that parents apply the basic rules of hygiene with respect to the handling of food and objects, to improve the conditions of health in the children of our population Saragurense.